2019
DOI: 10.1108/wjstsd-10-2018-0059
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and women in South Asia: a review and future policy implications

Abstract: Purpose South Asian region is a focal point owing to its vulnerabilities to climate-sensitive diseases, dependence on climate-sensitive livelihoods, projected levels of crop decline in the region, and high rates of poverty and malnutrition. Women are particularly vulnerable to climate change and this affects women disproportionately during different extreme events. The purpose of this paper is to understand the issue of climate change and its impact, and climate resilience among women in South Asia. Further, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Previous studies (Gender and Alliance, 2016;Buckingham and Le Masson, 2017;Pearse, 2017) revealed that gender is positively related to climate change. Women, particularly those who are poor and are in rural areas have been found to be disproportionately and adversely impacted by climate change compared to males (Tanny and Rahman, 2016;Patel et al, 2019). Our findings concur with the findings by Selm et al (2019) where women were found to have a negative self-perception of climate change knowledge.…”
Section: Farmers' Perception On Climate Changesupporting
confidence: 86%
“…Previous studies (Gender and Alliance, 2016;Buckingham and Le Masson, 2017;Pearse, 2017) revealed that gender is positively related to climate change. Women, particularly those who are poor and are in rural areas have been found to be disproportionately and adversely impacted by climate change compared to males (Tanny and Rahman, 2016;Patel et al, 2019). Our findings concur with the findings by Selm et al (2019) where women were found to have a negative self-perception of climate change knowledge.…”
Section: Farmers' Perception On Climate Changesupporting
confidence: 86%
“…Despite this recognition, the need for improved integration of ILK and scientific knowledge-also termed "bridging knowledge systems" ( Adapted from: Nadeem et al, 2009;Nyong et al, 2007;Pandey et al, 2003;Patel, 2020;Rivera-Ferre et al, 2013;UNPFII, 2007. Table 3 offers an overview of how current National Adaptation Plans (NAPs) in the 10 assessed case-study countries have currently integrated and dealt with ILK. It shows that many NAPs recognize the need to integrate ILK and explicitly list this in the official documents.…”
Section: Ilk Is Widely Recognized By the Intergovernmental Science-po...mentioning
confidence: 99%
“…Climate change also presents an unprecedented public health challenge as it has a great impact on population health outcomes (physical and psychological) and on different demographic groups across all continents [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%